Relationship between training load, neuromuscular fatigue, and daily well-being in elite young wrestlers - Yildiz, M.; Akyildiz, Z.; Gunay, M.; Clemente, F. M. (Research Quarterly for Exercise and Sport, 2024)
Purpose This study investigated acute workload (wAW), chronic workload (wCW), acute: chronic workload ratio (wACWR), training monotony (wTM), perceived load training strain indicators (wTS), and countermovement jump (CMJ) as indicators of wellness in one season and defined weekly variations. In addition, we analyzed the relationships between training load measurements and weekly reports.